Micro/Nanorobot: A Promising Targeted Drug Delivery System - Mengyi Hu; Xuemei Ge; Xuan Chen; Wenwei Mao; Xiuping Qian; Wei-En Yuan (Pharmaceutics, 2020)
Micro/nanorobot, as a research field, has attracted interest in recent years. It has great potential in medical treatment, as it can be applied in targeted drug delivery, surgical operation, disease diagnosis, etc. Differently from traditional drug delivery, which relies on blood circulation to reach the target, the designed micro/nanorobots can move autonomously, which makes it possible to deliver drugs to the hard-to-reach areas. Micro/nanorobots were driven by exogenous power (magnetic fields, light energy, acoustic fields, electric fields, etc.) or endogenous power (chemical reaction energy). Cell-based micro/nanorobots and DNA origami without autonomous movement ability were also introduced in this article. Although micro/nanorobots have excellent prospects, the current research is mainly based on in vitro experiments; in vivo research is still in its infancy. Further biological experiments are required to verify in vivo drug delivery effects of micro/nanorobots. This paper mainly discusses the research status, challenges, and future development of micro/nanorobots.